Android-Based WUZARU Media Boosts Science Learning in Elementary Students: Media WUZARU Berbasis Android Dorong Pembelajaran Sains pada Siswa SD - Vivi Dwi Permatasari; Fitria Nur Hasanah (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Elementary science education often struggles with abstract topics like